The relationship between nutritional knowledge and dietary adherence of people with diabetes mellitus - Fitri Yani Arbie; Nuryani Nuryani; Ayu Bulan Febry; Vera Tasintimbang Harikedua; Nonce Nova Legi; Fatmayanti Nawa (Poltekkes Kemenkes Aceh, 2025)
Background: Knowledge of nutrition and adherence to diet affects the healing process and health status of individuals with diabetes mellitus.Objectives: To determine the level of nutritional knowledge and dietary compliance of patients with diabetes mellitus (DM).Methods: This study used a quantitative approach with a descriptive study design and was conducted at a community health center in the Gorontalo City area from March to August 2024. Purposive sampling of 141 respondents was conducted. Diet adherence was measured using the Perceived Dietary Adherence Questionnaire (PDAQ), whereas knowledge was assessed using the Diabetes Knowledge Questionnaire (DKQ), which was analyzed using descriptive frequency.Results: The results of the knowledge measurement study show that 36,2% of the participants had low knowledge, while 78,7% had a low level of compliance. The PDAQ analysis showed the highest score regarding compliance in fish consumption (score=6,5±1,1), while the lowest score pertained to compliance in the selection and use of healthy oils (olive oil and organic oil) (0,3±1,2).Conclusion: A low level of knowledge can affect the dietary compliance of patients with DM.